A Magnetorheological Fluid Damper for Rotor Applications. (2004) - Forte, P.; Paternò, M.; Rustighi, E.
Abstract : Even though we are still far from industrial applications, in the last decade there has been increasing attention directed toward the employment of electrorheological (ER) and magnetorheological (MR) fluids in active bearings and active squeeze film dampers in rotordynamics. MR fluids react to magnetic fields undergoing reversible changes in their mechanical characteristics, viscosity, and stiffness in particular. In previous literature, some applications of ER fluids in rotor squeeze film dampers can be found; however, on the contrary, little is reported on similar test rigs set up for MR dampers. In this work, the design of an MR squeeze film damper is presented and discussed. A numerical simulation has been carried out in order to evaluate the dynamic behavior of the damped rotor as a function of the magnetic field strength. The test rig is made of a slender shaft supported by two oilite bearings and an unbalanced disk. The damper is interfaced with the shaft through a rolling bearing. Electric coils generate the magnetic field whose field lines cross the MR film. Since the damping characteristics can be varied continuously by controlling the magnetic field, it is possible to have the optimum conditions for each regime of rotational speed. Preliminary tests are encouraging.